Anestesi Tetes Infus Gravimetrik Ketapol sebagai Alternatif Bius Umum Secara Inhalasi Guna Menjaga Status Teranestesi pada Babi - Pemayun, I Gusti Agung Gde Putra; Sudisma, I Gusti Ngurah (Jurnal Veteriner; Vol 19 No 1 (2018)DO - 10.19087/jveteriner.2018.19.1.126, 2018)
This study aim was to evaluate quality and effectiveness of anaesthesia by using gravimetric infusion anaesthesia with ketamine and propofol (ketafol) on pigs. The quality of anesthesia time, the cardiovascular and respiratory response of anaesthesia were evaluated in twelve male pigs with average body weight 35±5 kg. The pigs were divided into four treatments and each treatment consisted of three pigs as repetition. All the experimental animals were premedicated with atropine 0.03 mg/kg mixed with xylazine 2 mg/kg in one syringe injected intramuscularly. Fifteen minutes after premedicated, the pigs was induced intravenously with ketamine 6 mg/kg and propofol 2 mg/kg. Furthermore, the anesthetized state maintaned with gravimetric, each through infusion with propofol (0.1 mg/kg/minute) (PI-P) , ketamine (0.3 mg/kg/ minute) (PIK), combination propofol-ketamin (0.1 and 0.3 mg/kg/minute) (PI-PK), and inhalation with isoflurane 1-2% (PI-I). The heart rate, pulse, respiratory rate, rectal temperature, blood oxygen saturation (SpO2 ), capillary refill time (CRT) were observed before and after treatment of the anesthetic. Premedication combination of atropin 0.03mg/kg mixed with xylazine 2 mg/kg in one syringe and then induced with ketamine 6 mg/kg and propofol 2 mg/kg showed the average length of anesthesia for 32,33 minutes, longer compared to five other treatments with average length of induction three minutes and average recovery time 20.33 minutes. Maintenance of anesthesia with propofol infusion drops (0.1 mg/kg/minute), or propofolketamine infusion drops (0.3 and 0.1 mg/kg/minute) showed safer anesthesia, because they did not make drastic change of heart rate, respiratory rate, rectal temperature, oxygen saturation, pulse, and CRT value in the experimental pigs. The conclusion of this study is the methode of gravimetric intravenous infusion by using ketamine and propofol (ketafol) can be used to maintain anesthesia as an alternative general inhalation anaesthesia in pigs.